PENGEMBANGAN KAPASITAS PRODUKSI PETANI JAMUR TIRAM DESA PUNGGUL KECAMATAN GEDANGAN KABUPATEN SIDOARJO - Hendro Sutowijoyo; I.G.A. Nitja Aju Dharmani; Adhi Muhtadi (Universitas Negeri Surabaya, 2026)
Oyster mushrooms are a food ingredient with numerous benefits, including being a source of biological protein, fiber, vitamins, and minerals, and possessing anticancer properties. The numerous benefits of oyster mushrooms make them a highly sought-after food ingredient in local markets in Sidoarjo Regency. The challenge faced is the steamer's small capacity, resulting in a low yield of only 9.4 kg per day. This yield is immediately purchased by local market traders. Meanwhile, some of the roof frames and baglog racks have decayed. Therefore, the purpose of this community service activity is to increase the capacity of the mushroom steamer and also repair the decayed roof frame and baglog racks. This activity method consists of outreach activities, steamer selection, training, technology application, and evaluation of mushroom production results. The steamer's original capacity was only 100 baglogs per week, while the new steamer has a capacity of 500 baglogs per week. The roof frame and baglog racks have also been repaired so that they will not endanger mushroom farmers from being hit by a collapsed roof, and the oyster mushroom racks can accommodate more baglogs. Oyster mushroom yields have been proven to increase to 28 kg per day. This community service program will help increase the income of mushroom farmers in Punggul Village, Gedangan District, Sidoarjo Regency. It is also expected to contribute to local poverty alleviation through resource-based initiatives.